Randomized controlled trial of brief cognitive-behavioural interventions among regular users of amphetamine - Baker, Amanda; Boggs, Tracy G.; Lewin, Terry J. (Addiction (Abingdon, England), 2001)
Aims. To identify whether brief cognitive‐behavioural interventions are feasible among regular users of amphetamine, to assess the effectiveness of intervention overall and to pilot two‐ and four‐session interventions. Design. Subjects were assigned randomly to individually receive a cognitive‐behavioural intervention ( n = 32) of either two or four sessions' duration or a self‐help booklet (control condition; n = 32). Setting. Subjects were volunteers recruited from needle exchange schemes and treatment centres in Newcastle, Australia. Participants. Regular (at least monthly) users of amphetamine were recruited. Intervention. Either four sessions of cognitive‐behaviour therapy, consisting of a motivational interview and skills training in avoidance of high‐risk situations, coping with craving and relapse prevention, or two sessions consisting of a motivational interview and discussion of skills. Measurements. The Opiate Treatment Index was the main measure at pre‐treatment and 6‐month follow‐up. Findings. There was a significant reduction in amphetamine use among the sample as a whole, with inconclusive differences between intervention subgroups. There was a moderate overall intervention effect, with the intervention group reporting over twice the reduction in daily amphetamine use as the control group. Significantly more people in the cognitive‐behavioural intervention condition abstained from amphetamine at 6‐month follow‐up compared to the control condition. Conclusion. Brief cognitive‐behavioural interventions appear feasible among regular users of amphetamine. A larger randomised controlled trial of the effectiveness of such interventions appears warranted.